First-Arrival Differential Counting for SPAD Array Design - Mel White; Tianyi Zhang; Akshat Dave; Shahaboddin Ghajari; Alyosha Molnar; Ashok Veeraraghavan (Sensors, 2023)
We present a novel architecture for the design of single-photon detecting arrays that captures relative intensity or timing information from a scene, rather than absolute. The proposed method for capturing relative information between pixels or groups of pixels requires very little circuitry, and thus allows for a significantly higher pixel packing factor than is possible with per-pixel TDC approaches. The inherently compressive nature of the differential measurements also reduces data throughput and lends itself to physical implementations of compressed sensing, such as Haar wavelets. We demonstrate this technique for HDR imaging and LiDAR, and describe possible future applications.